THE TEACHING PRAXIS WITH LITERARY READING: CONTRIBUTIONS TO HUMAN DEVELOPMENT AND EMANCIPATION - Santos Klem, Suelen Cristina dos; Granado Sanches, Gislaine Gomes; Coelho de Paiva Balca, Angela Maria Franco Martins; Pires Franco, Sandra Aparecida (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
The article is the result of work carried out with the discipline of Education, human formation and praxis: implications of Historical-Cultural Theory and of Historical-Critical Pedagogy for School Education of the Graduate Program in Master of Education at the State University of Londrina (UEL). The objective was to present contributions of teaching practices in the school environment, with a view to human and social development from the work with Literary Reading. It was based on the problem: how Literary Reading can contribute to the teaching praxis and for the development and human emancipation of the student? It is a critical-dialectical approach with qualitative data treatment. Data generation consisted of conducting bibliographic research. As results and discussions, we understand that the teaching praxis, when intentionally planned, provides the development and human emancipation, because Literary Reading has contributions in relation to language, the criticality and conscience of the reader.
Keywords: Education; Literary reading; Teaching praxis; Development and human emancipation